Respuesta :

Solution:

[tex]\frac{3x}{2x-6}+\frac{9}{6-2x}\\\\ =\frac{3x}{2x-6}+\frac{9}{-1(2x-6)}\\\\= \frac{3x}{2x-6}+\frac{-9}{2 x-6}\\\\ =\frac{3x-9}{2x-6}\\\\=\frac{3(x-3)}{2(x-3)}\\\\ =\frac{3}{2}[/tex]

a= -1

b= -9

c= 9

d=3

e= 3

f=2

g= [tex]\frac{3}{2}[/tex]

The values for the highlighted variables are: a = -1, b = 9, c = 9, d = 3, e = 3, f = 2 and g = 1.5. And the sum of the variables is equal to 26.5.

Given :

Equation - [tex]\dfrac{3x}{2x-6}+\dfrac{9}{6-2x}[/tex]

Taking -1 common from (6-2x) in the above equation:

[tex]\dfrac{3x}{2x-6}+\dfrac{9}{6-2x} = \dfrac{3x}{2x-6}+\dfrac{9}{-1(2x-6)}[/tex]  ---- (1)

By compairing the above equation with the given data, the value of a = -1 and b = 9.

Now, further simplify equation (1).

[tex]\dfrac{3x}{2x-6}+\dfrac{9}{6-2x} = \dfrac{(3x-9)}{(2x-6)}[/tex]  ---- (2)

By compairing the above equation with the given data, the value of c = 9.

Now, from equation (2) taking 2 common from the denominator and taking 3 common from the numerator.

[tex]\dfrac{3x}{2x-6}+\dfrac{9}{6-2x} = \dfrac{3(x-3)}{2(x-3)}[/tex]    ----- (3)

By compairing the above equation with the given data, the value of d = 3, e = 3 and f = 2.

Now, from equation (3), (x-3)  will be cancel out.

[tex]\dfrac{3x}{2x-6}+\dfrac{9}{6-2x} = \dfrac{3}{2}[/tex]

By compairing the above equation with the given data, the value of g = 1.5.

The sum of the unknown variables = a + b + c + d + e + f + g

= -1+9+9+3+3+2+1.5  = 26.5

For more information, refer the link given below

https://brainly.com/question/12420841